2015
DOI: 10.1016/j.socscimed.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating structural vulnerability following regulatory changes to a provincial methadone program in vancouver, canada: A qualitative study

Abstract: While regulatory frameworks governing methadone maintenance therapy (MMT) require highly regimented treatment programs that shape treatment outcomes, little research has examined the effects of regulatory changes to these programs on those receiving treatment, and located their experiences within the wider context of socialstructural inequities. In British Columbia (BC), Canada, provincial regulations governing MMT have recently been modified, including: replacing the existing methadone formulation with Methad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 53 publications
5
55
1
Order By: Relevance
“…Once the final thematic categories were established, data were recoded to ensure their trustworthiness. The concept of structural vulnerability was employed when interpreting these themes to focus attention on how social-structural factors and sociocultural processes produced treatment fatigue [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the final thematic categories were established, data were recoded to ensure their trustworthiness. The concept of structural vulnerability was employed when interpreting these themes to focus attention on how social-structural factors and sociocultural processes produced treatment fatigue [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
“…The concept of structural vulnerability focuses attention on how the interplay of structural inequities (e.g., disparities in incarceration rates under drug criminalization, housing instability) and socio-cultural processes (e.g., racism, sexism) render marginalized populations susceptible to harm [31, 32], and is particularly useful in understanding adverse ART outcomes among PWUD. For example, previous studies have demonstrated that factors associated with structural vulnerability, such as incarceration and homelessness [33, 34], contribute to ART discontinuation among PLHIV who use drugs in Vancouver, Canada, a setting with a community-wide TasP initiative.…”
Section: Introductionmentioning
confidence: 99%
“…drug criminalization, racism, poverty, sexism), as well as institutional structures (e.g. policies, regulations) (McNeil et al, 2015; Quesada, Hart, & Bourgois, 2011). Researchers and research ethics boards recognize that compensation incentivizes participation (Ripley et al, 2010) and may prompt PWUD and other structurally vulnerable populations to engage in low or high-risk research primarily out of financial need (Dickert & Grady, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Social-structural forces operating within hospitals often deny the subjective health experiences and agency of ‘structurally vulnerable’ patient populations. These populations occupy marginal positions within social hierarchies due to social-structural inequities (e.g., drug criminalization, racism) and institutional arrangements (e.g., policies and practices), which render them vulnerable to adverse outcomes (28,29). For example, institutionalized racism within hospital settings often constrains patient-centered communication and shared decision-making for racialized populations (e.g., Indigenous or African-American populations) (23,30,31).…”
Section: Introductionmentioning
confidence: 99%